Lindavia biswashanti, a new diatom species (Bacillariophyta) from Gokyo Cho, Himalayan Range, Nepal - Mohan, Joseph; Stone, Jeffery R; Nicholson, Kirsten; Neumann, Klaus; Dowling, Carolyn; Sharma, Subodh (Phytotaxa, 2018)
A new species of Bacillariophyta (diatom) is described from Gokyo Cho, a lake near Mount Everest in the Himalayan Mountain Range. Water and algal samples were collected during an expedition to Sagarmatha National Park (SNP), Nepal in May 2016. Samples collected during this expedition reveal a new species of Lindavia, described herein with ecological information provided. The new species of Lindavia has three triangular undulations and depressions in the central area. This species has a likeness to the Pantocsekiella ocellata sensu lato group. It differs from the species in this group in undulation shape and ultrastructure numbers and distribution. Investigation into previously described Lindavia in the SNP region has identified a taxon, Cyclotella antiqua var. minor, which is herein transferred into Lindavia in order to conform to the parent taxon Lindavia antiqua.